El LIENE avanza hacia una turbina eólica adaptada al viento de Costa Rica - Richmond-Navarro, Gustavo (2025)
The LIENE lab (Laboratorio de Investigación en Energía Eólica) of the Department of Electromechanical Engineering at the Instituto Tecnológico de Costa Rica is working on the development of a wind turbine rotor adapted to the particular wind conditions of Costa Rica. This effort began in 2018 with the installation of meteorological towers to characterize the country’s wind resource. Based on the obtained data, a literature review was carried out on aerodynamic profiles suitable for the predominant flow type. On that basis, an experimental rotor was designed, later manufactured, and tested under controlled laboratory conditions. The results showed improvements of up to 218% compared to a commercial rotor. In the future, the research will focus on studying the optimal number of blades, refining the aerodynamic design, and achieving efficient coupling between the rotor and the electric generator.